2022
DOI: 10.1007/s10763-022-10294-2
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Error-handling Practices Within and Across Lesson Phases in the Mathematics Classroom

Abstract: Multiple studies have been conducted regarding teachers’ error-handling practices, and how errors can be treated as opportunities for learning, albeit in the context of whole-class discussions. The aim of the present research is to continue to investigate teachers’ error-handling practices as they occur in different phases of maths lessons: introduction of the task, when students are working alone, and when students are working in pairs and finally, as part of the whole-class discussion. The study included 51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, students think that if they write down what they know and what they ask, they don't need to write it down in the solution, this happens to Low Subjects (SR). The factor that causes this error to be made by students is because students do not understand the concept of the material that has been taught previously (Kaufmann et al, 2023); (Hakimi et al, 2024). This happened to SR 3.…”
Section: Resultsmentioning
confidence: 99%
“…However, students think that if they write down what they know and what they ask, they don't need to write it down in the solution, this happens to Low Subjects (SR). The factor that causes this error to be made by students is because students do not understand the concept of the material that has been taught previously (Kaufmann et al, 2023); (Hakimi et al, 2024). This happened to SR 3.…”
Section: Resultsmentioning
confidence: 99%
“…Slips and errors are distinguished by Gardee and Brodie (2021). It is found that errors mainly occur at a deeper conceptual level than slips (Kaufmann et al, 2022). Gardee and Brodie (2015) add that errors are systematic and caused by misconceptions, due to overgeneralisation of prior knowledge.…”
Section: Introductionmentioning
confidence: 93%
“…Finzer and Bennett (1995) describe errors as learners' incorrect answers in addressing the problem at hand and caused by following incorrect procedures to solve those problems in mathematics. Kaufmann et al (2022) view errors as mistakes, slips or misunderstanding of learners when solving mathematical problems. Slips and errors are distinguished by Gardee and Brodie (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Slips and errors are distinguished by Gardee and Brodie (2021). It is found that errors mainly occur at a deeper conceptual level than slips (Kaufmann et al, 2022). Gardee and Brodie (2015) add that errors are systematic and caused by misconceptions, due to overgeneralization of prior knowledge.…”
Section: Errors In Learning Mathematicsmentioning
confidence: 99%